Constituting the political economy of the Kurds : social embeddedness, hegemony, and identity - Tekdemir, Omer (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This book examines the development of Kurdish political economy and the emergence of collective Kurdish identity within a historical context through three main periods: the late- Ottoman Empire, the initial Republican Turkey era and then the post-1990s period. It relates historical developments to the dynamics of Kurdish society, including the anthropological realities of the nineteenth century through the moral economy frame, the evolving nature of nationalism in the early twentieth century and the more recent construction of a modern political Kurdishness by means of radical democracy, and an agonistic pluralism shaped by left-wing populism"--
Introduction: Emerging power in the changing Middle East -- Methodology within the Kurdish narrative -- The political economy origins of Kurds in the Ottoman Empire -- Kurdish moral economy : historical perspectives on embeddedness -- Counter-hegemonic society in the Republic of Turkey -- Passive revolution : constructing institutional politics -- National identity : many Kurds in agonistic pluralism -- Articulating an alternative discourse in the EU-ised sphere -- A Kurdish model : embeddedness, radical democracy and populism.
"Published in association with the Sheikh Nasser al-Mohammad al-Sabah Programme at Durham University."
OCLC-licensed vendor bibliographic record.
Keywords: Kurds -- Turkey -- Politics and government; Kurds -- Turkey -- Social conditions; Turkey -- Politics and government; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Research